Adaptation of The Wiruncana Murca Play in The Wayang Topeng Jatiduwur (Jatiduwur Mask Puppet) Jombang Performance (Harmonia: Journal of Arts Research and Education, 2020)
Wiruncana Murca play is the only Panji play in the Mask Puppet Performance in Jatiduwur Jombang which still performances its dramatic structure after the Mask Puppet is extinct. Wiruncana Murca play in the Wayang Topeng Jatiduwur Performance in the past was used for nadzar rituals. When the Mask Puppet was rebuilt, the Wiruncana Murca play was performed in a different context, the Panji Festival. This study aims to analyze the transformation process of the Wiruncana Murca play with an adaptation approach. The scope of this research includes text and context. The research method is descriptive qualitative analytical. The data collection used is observation, interview, and document study. The analysis uses an analytical descriptive method. The results performance that the adaptation of Wiruncana Murca in the Wayang Topeng Jatiduwur performance was carried out because there was a different contextuality from the ritual cultural context of the Jatiduwur village community to the context of the National Panji Festival performance in 2017 in Kediri. The transformation was carried out by the stages of identification of story ideas, the embodiment of the text, the embodiment of the dramaturgy, and staging. Adaptation to the process of intellectual transformation is based on a new contextual approach using fidelity or maintaining the originality of the source. The original uniqueness of the existing art is still used as a source of inspiration or a source of reference used as material to develop new performance products. The adaptation of the Wiruncana Murca play in the context of the Wayang Topeng Jatiduwur performance at the 2017 National Panji Festival performances the creative process of mask artists. While the result is a manifestation of a new product from Mask Puppet in Jatiduwur Jombang.